Recent evolution in Baltic Fucus vesiculosus: reduced tolerance to emersion stresses compared to intertidal (North Sea) populations - Pearson, G. A. (2014)
The Baltic is a young, brackish and non-tidal sea, supporting an impoverished marine flora compared with adjacent open coastal areas. Populations of the normally intertidal brown alga Fucus vesiculosus L. are permanently submerged in the Baltic. We tested the hypothesis that these populations have evolved a reduced ability to withstand water-stresses caused by aerial exposure (desiccation and freezing), relative to adjacent intertidal populations in the North Sea. Desiccation and freezing tolerance were compared using chlorophyll fluorescence to monitor photosynthetic status during stress and recovery. To control for the influence of growth salinity on stress tolerance, the experimental material consisted of either adult algae cross-acclimated at Baltic and North Sea salinities(6.5 and 20 to 24 practical salinity units [psu], respectively), or juveniles from both populations grown in the Baltic from embryos (submersed, 6.5 psu). Baltic algae were less able to recover maximum photochemical yield (Fv/Fm) after freezing at –15°C than North Sea algae, and neither acclimation(adults) or growth salinity (juveniles) accounted for between-population differences. During desiccation at 5°C, differences in the response of variable fluorescence (Fv), as well as in initial fluorescence (F0) and Fv during recovery, indicated that impaired photoprotective processes may contribute to the inability of Baltic algae to fully recover Fv/Fm after stress, in contrast to North Sea algae which displayed dynamic and rapidly recoverable reductions of Fv/Fm. Subsequent desiccation experiments during the summer (at 25°C) showed that, relative to North Sea algae, the effective photochemical yield (DF/Fm’) of Baltic algae started to decline at lower tissue-water content (TWC) and recovered less completely after a return to seawater. A critical TWC of ca 10% for Baltic populations was identified, below which DF/Fm’ did not fully recover. In addition, Baltic algae were less able to regain initial TWC during recovery. These results indicate that, in ca 7500 yr since the recruitment of the present marine flora to the Baltic, F. vesiculosus has evolved reduced tolerance to emersion stresses compared to adjacent intertidal populations.